2018
DOI: 10.1158/1538-7445.am2018-5245
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5245: Identification and characterization of the IDO1 inhibitor LY3381916

Abstract: Indoleamine 2,3-dioxygenase 1 (IDO1) is a heme-dependent enzyme that catalyzes the initial and rate-limiting step of tryptophan catabolism resulting in the local depletion of tryptophan and the concomitant production of kynurenine, both of which are immunosuppressive. Targeting IDO1 in combination with PD-1/PD-L1-targeted antibodies has shown promise in early phase clinical trials in several cancers and strongly suggests that, in some patients, IDO1 expression restrains PD-1/PD-L1-targeted checkpoint therapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Recently pharmacodynamics data from a preclinical study in solid tumours were released, which revealed that LY3381916 does not bind the mature IDO1 enzyme but rather binds to the haem-binding pocket of the apo-IDO1 protein, thus preventing protein maturation. 151 …”
Section: Trp-catabolising Enzymes (Tce)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently pharmacodynamics data from a preclinical study in solid tumours were released, which revealed that LY3381916 does not bind the mature IDO1 enzyme but rather binds to the haem-binding pocket of the apo-IDO1 protein, thus preventing protein maturation. 151 …”
Section: Trp-catabolising Enzymes (Tce)mentioning
confidence: 99%
“…Such data are not available for epacadostat. Evaluation of the intra-tumoural concentrations of epacadostat would be important, as intra-tumoural penetrance of IDO1 inhibitors could be hindered due to diminished blood supply 143 , 151 or elevated oncotic pressure in solid tumours 8 , 143 (Fig. 2a , left).…”
Section: Trp-catabolising Enzymes (Tce)mentioning
confidence: 99%
“…(A) Current mechanistic proposals for IDO/TDO-mediated oxidative cleavage of tryptophan, where the initial indole activation is either by an electrophilic or radical addition . (B) Representative hIDO1/hTDO inhibitors: epacadostat (INCB024360), navoximod (NLG-919), I-1 , linrodostat (BMS-986205), , PF-06840003, LY3381916, NLG8189, I-2 , I-3 , LM10, I-4 , I-5 , I-6 , I-7 , I-8 , and I-9 , of which the potency values are from the corresponding cited references.…”
Section: Introductionmentioning
confidence: 99%
“…Since hIDO1 inhibitors have great potential for cancer immunotherapy other than CNS disorders, a number of highly potent and selective hIDO1 inhibitors have been developed, many of which have entered clinical development, such as epacadostat (INCB024360), navoximod (NLG-919), linrodostat (BMS-986205), PF-06840003, and LY3381916 (Figure B). Very recently, several structurally novel hIDO1 inhibitors (e.g., I-1 , I-2 , and I-3 ) were continuously identified by the DNA-encoded library technology, virtual screening, or other strategies (Figure B), providing new candidates for drug development. Mechanistic studies of hIDO1 inhibitors have revealed distinct inhibition modes, for example, via binding to chelate with heme iron, , binding to heme without iron chelation, binding to trigger heme release, , or only binding with apo -hIDO1, suggesting different perspectives in inhibitor development.…”
Section: Introductionmentioning
confidence: 99%
“…Indoleamine 2,3-dioxygenase-1 (IDO1), indoleamine 2,3-dioxygenase-2 (IDO2), and tryptophan 2,3-dioxygenase (TDO) are the first rate-limiting enzymes in the KP that catalyze the conversion of Trp to kynurenine (Kyn). IDO1, the most well-characterized enzyme, is frequently overexpressed in the vast majority of cancers, and IDO1 overexpression is associated with poor prognosis. , Extensive preclinical evidence has demonstrated that IDO1-expressing dendritic cells (DCs) mediate immune tolerance mainly via the degradation of Trp and its metabolites, which results in the inhibition of effector T cell proliferation and the induction of regulatory T cell (Treg) differentiation and activation. Therefore, the development of IDO1 inhibitors as immunotherapeutic agents has attracted considerable attention. Several selective and highly potent IDO1 inhibitors have been developed, and some of them have successfully advanced into clinical trials as a single agent or in combination with other drugs in the past decade, such as navoximod (NLG919), epacadostat (Epa), linrodostat (BMS-986205), PF-06840003, and LY3381916 (Figure ). Due to the failure of Epa to improve clinical responses in a phase III trial (ECHO-301), many efforts have been made to search for novel and more potent IDO1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%